1996
DOI: 10.1177/096032719601501202
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation and uptake of paraquat by rat renal proximal tubular cells in primary culture

Abstract: 1 Uptake of the herbicide paraquat (PQ), by rat proximal tubular cells (PTC) in primary culture grown on a collagen coated support was investigated. 2 The uptake of PQ by PTC was predominantly from the basolateral side. The basolateral uptake of PQ was saturable with time and increasing concentrations, energy dependent and could be inhibited by certain organic cations. Using Michaelis Menten kinetics, the apparent Km was 778 ± 241 μM and Vmax was 0.97 ± 0.24 pmol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 31 publications
4
6
0
Order By: Relevance
“…This uptake of paraquat is saturable with time and with increasing concentration of paraquat. It is also energy-dependent and is inhibited by certain polyvalent cations, such as quinine, cimetidine, and methylglyoxal bis(guanylhydrazine) dihydrochloride [36], [58] and [59]. The inhibitory effect of cimetidine, a divalent ion, on the uptake of paraquat into NRK-52E cells as has been shown in this study indicates the presence of a polyvalent OCT protein on NRK-52E cells and that this OCT is used by paraquat to enter NRK-52E cells.…”
Section: Discussionsupporting
confidence: 71%
“…This uptake of paraquat is saturable with time and with increasing concentration of paraquat. It is also energy-dependent and is inhibited by certain polyvalent cations, such as quinine, cimetidine, and methylglyoxal bis(guanylhydrazine) dihydrochloride [36], [58] and [59]. The inhibitory effect of cimetidine, a divalent ion, on the uptake of paraquat into NRK-52E cells as has been shown in this study indicates the presence of a polyvalent OCT protein on NRK-52E cells and that this OCT is used by paraquat to enter NRK-52E cells.…”
Section: Discussionsupporting
confidence: 71%
“…The present data did not show saturation of the paraquat transport probably because of the low paraquat concentrations used. This observation is supported by other studies in rabbit renal proximal tubules and rat renal tubular cells in primary culture showing saturation at concentrations about 300 pM paraquat (Groves et al 1995;Chan et al 1996). In human lung tissue, saturation of paraquat transport was reached at 5 mM paraquat (Hoet et al 1994), a concentration which causes severe reduction of renal proximal tubular oxygen consumption (Mslck & Friis 1997).…”
Section: Discussionsupporting
confidence: 76%
“…Additionally, transport was inhibited by organic cations, including quinine, cimetidine, and TEA, with no change observed in the presence of organic anions. Similar results were demonstrated in primary rat proximal tubule cells [105]. Mechanistic transport studies using HEK293 cells overexpressing human OCT1, 2, or 3 revealed that overexpression of OCT2, but not OCT1 or OCT3, enhanced the accumulation (12-fold) and cytotoxicity (18-fold) of PQ [57].…”
Section: Prototypical Nephrotoxicantssupporting
confidence: 60%